Experimental and numerical study on tensile strength and failure pattern of high performance steel fiber reinforced concrete under dynamic splitting tension - Li, Xiaojing; Zhang, Yaoyao; Shi, Chong; Chen, Xudong (Construction & building materials, 2020)
•Dynamic response and enhancement mechanism of HPSFRC were investigated.•The effect of strain rate on fiber reinforced factor and dynamic increase factor was studied.•The effects of steel fiber content and strain rate on energy dissipation ratio were analyzed.•LS-DYNA was used to reproduce the crack propagation process in the HPSFRC specimen. High performance steel fiber reinforced concrete (HPSFRC) is widely used in structural engineering due to its excellent performance. It is necessary to study its dynamic mechanical properties for making full use of the material, reducing the engineering cost and optimizing the structural design. Firstly, the dynamic splitting tensile tests of HPSFRC with different fiber contents (0%, 1%, 2%) were conducted by using a 74 mm-diameter splitting Hopkinson pressure bar (SHPB) system under different strain rates (70/s ~ 190/s). Then, according to failure pattern of the specimen and test data, the enhancement mechanism of strain rate and steel fiber on tensile stress of HPSFRC is analyzed, relationship between strain rate and dynamic splitting tensile strength increase factor (DIFft) is also discussed. Furthermore, the enhancement mechanism of steel fiber and strain rate on HPSFRC is verified based on energy conversion during failure process. Finally, the dynamic failure process of HPSFRC is simulated by LS-DYNA, and failure patterns of HPSFRC with different fiber contents are compared from the perspective of crack development. The results indicate that the energy dissipation ratio increases with the ascending steel fiber content and decreases with the ascending strain rate. The steel fiber can increase tensile stress of HPC, and the enhancement degree under quasi-static loading is better than that under dynamic loading. In addition, steel fiber reinforced factor and DIFft have strain-rate effect. Steel fiber reinforced factor decreases as strain rate increases. On the contrary, DIFft increases as strain rate increases, and the increasing trend gradually slows down. These results can provide a basis for improving the dynamic tensile properties of HPSFRC.